Aktualisasi Al-QawÄâ€™id Al-Khams terhadap Problematika Kontemporer - Ashar, Ashar (IAIN Samarinda, 2014)
The canon of interpretation in Islamic jurisprudence (al-qawa`id al-fiqhiyah) is like a bridge for an Islamic Jurist (faqih) to find a common thread in analyzing and deciding the extent of the legal problems. It also serves as the meeting point of the Islamic-jurisprudence-related issues. This is what makes an Islamic Jurist wiser and more sensible in applying fiqh at different times and places. When they provide an interpretation on a similar case, they take into account the situation and condition, as well as different customs. At the level of actualization, al-Qawa'id al-Khams can be applied to almost all of the discussion in the discourse of Islamic jurisprudence. The five rules of fiqh are always used as the base and backrest each Islamic Jurists in providing answers and solutions to various problems of life since the classical time to present.